1998
DOI: 10.1093/nar/26.22.5139
|View full text |Cite
|
Sign up to set email alerts
|

Identity elements and aminoacylation of plant tRNATrp

Abstract: Mutation of the Arabidopsis thaliana tRNA (Trp)(CCA) anticodon or of the A73 discriminator base greatly diminishes in vitro aminoacylation with tryptophan, indicating the importance of these nucleotides for recognition by the plant tryptophanyl-tRNA synthetase. Mutation of the tRNA (Trp)(CCA) anticodon to CUA so as to translate amber nonsense codons permits tRNA (Trp)(CCA) to be aminoacylated by A.thaliana lysyl-tRNA synthetase. Thus, translational suppression by tRNA (TRP)(CCA) observed in plant cells include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…We previously demonstrated that tRNA Trp (CUA) is aminoacylated in vivo by elevated levels of AtKRS‐1 (Ulmasov et al. , 1998), and here have established that transient or stable expression of AtKRS‐1 promotes significant recoding by suppressor tRNA Lys and also significant incorporation of lysine into zeins.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…We previously demonstrated that tRNA Trp (CUA) is aminoacylated in vivo by elevated levels of AtKRS‐1 (Ulmasov et al. , 1998), and here have established that transient or stable expression of AtKRS‐1 promotes significant recoding by suppressor tRNA Lys and also significant incorporation of lysine into zeins.…”
Section: Discussionmentioning
confidence: 56%
“…The limitations of transient assays with reporter genes prevent sensitive measurement of recoding caused by ectopic expression of AtKRS alone; however, recoding can be detected in conjunction with ectopic expression of suppressor tRNA(CUA) species (Ulmasov et al. , 1998).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The anticodon and the discriminator nucleotide are the major identity elements for TrpRS (6,7). Whereas the anticodon is a phylogenetically shared identity element, the discriminator nucleotide differs between bacteria and eukaryotes (6), which explains why the two TrpRSs cannot efficiently cross-aminoacylate the corresponding tRNA Trp species (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Cytosolic tRNA Trp CCA is aminoacylated by a eukaryotic tryptophanyl-tRNA synthetase (TrpRS) (4), whereas the mitochondrial-encoded tRNA Trp UCA is charged by a bacterial-type TrpRS (5). The CCA anticodon is a known identity element for both enzymes (6)(7)(8). It is clear, however, that the bacterial-type enzyme in mitochondria must be able to tolerate an UCA anticodon (5).…”
mentioning
confidence: 99%